Relationship between Parent Role, Friends Effect Association and Use of Mass Media with Risk Sexual Behavior in Adolescents at Senior High School 76 Jakarta - An’nisaa Eka Rahmawati; Ritanti (Nursing and Health Sciences Journal (NHSJ), 2021)
Adolescents are individuals with high curiosity, including sexual behavior. BKKBN findings in 2017 show that the age group of 15-17 years is the highest age of first dating and age 17 is the highest age of first sexual intercourse. This study aims to determine whether there is a relationship between the role of parents, peer influence and the use of mass media with risky sexual behavior in adolescents at SMAN 76 Jakarta. This study used cross sectional study and was conducted on 154 respondents through a simple random sampling method. Data collection uses questionnaires on the role of parents, peer influence, the use of mass media and risky sexual behavior that have been tested for validity and reliability. Statistical test results using Chi-Square showed a significant relationship between the role of parents with risky sexual behavior (p = 0.001), peer influence with risky sexual behavior (p = 0.001) and the use of mass media for risky sexual behavior (p = 0.001). It is recommended that schools collaborate with local health services in conducting health education, counseling or therapy related to the problem of risky sexual behavior in adolescents.